Pengaruh Ekspor Impor terhadap Perdagangan Internasional - Nur Ehan Irzawati; Rahmayani Rahmayani; Yola Rosiani (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
In today's world, international trade is important for many countries. Exports and imports, along with exports and imports, are two important factors in the movement of goods and services between countries. This article discusses in depth the impact of exports and imports on international trade through various research methods using secondary data. The main objective is how it affects the country's economy. The focus of this research is the important role of exports and imports in a country's economic development, job creation and capacity building. On the other hand, there are also negative consequences to consider,such as loss of trade and dependence on international markets. A full understanding of the impacts of exports and imports is essential for a country to develop appropriate international trade policies. Smart policies can multiply the benefits of exports and imports, reduce negative impacts, and encourage sustainable economic growth.